2022
DOI: 10.1371/journal.pone.0277476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with histidine and β-alanine on blood plasma metabolome of broiler chickens at different ages

Abstract: Histidine is an essential amino acid for broiler chickens and a precursor for the dipeptides carnosine and anserine, but little information is available about its metabolism in modern, fast-growing broilers. We used untargeted metabolomics to investigate the metabolic changes caused by the use of different standardized ileal digestible His:Lys ratios in broiler diets with and without β-alanine supplementation. A total of 2204 broilers were randomly divided into 96 pens of 23 birds each. The pens were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Our results indicated that the Arginine level in the peripheral plasma was signi cantly increased; the Histidine level also increased but not signi cantly (P = 0.076), which was probably due to the enhanced permeability of the BBB (blood brain barrier) to Histidine under environmental stress [34]. Arginine and histidine supplementation increased their blood plasma concentrations [35,36]. Thus, in this study, the increased levels of plasma arginine and histidine can be mainly attributed to the enhancement of their biosynthesis in the gut bacteria, and the reduction of arginine metabolism.…”
Section: Gut Microbiota Regulates Hippocampal Glutamatergic System In...mentioning
confidence: 67%
“…Our results indicated that the Arginine level in the peripheral plasma was signi cantly increased; the Histidine level also increased but not signi cantly (P = 0.076), which was probably due to the enhanced permeability of the BBB (blood brain barrier) to Histidine under environmental stress [34]. Arginine and histidine supplementation increased their blood plasma concentrations [35,36]. Thus, in this study, the increased levels of plasma arginine and histidine can be mainly attributed to the enhancement of their biosynthesis in the gut bacteria, and the reduction of arginine metabolism.…”
Section: Gut Microbiota Regulates Hippocampal Glutamatergic System In...mentioning
confidence: 67%
“…Histidine has an effect on the metabolites of various metabolic pathways. L-arginine has a vital role in reducing fat deposition by moderating lipid metabolism ( Fouad et al, 2013 ; Lackner et al, 2022 ). Taurine affects meat quality by enhancing the anti-oxidative capacity and lipid metabolism, particularly under heat stress ( Lu et al, 2019 ; Xu et al, 2019 ; Han et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Distance was measured using Euclidean Correlations and the Ward clustering algorithm. For analyzing the interaction of gender with hypoxic state, we used the multivariate analysis feature from MetaboAnalyst 5.0 34 , the study design of 'two-factor independent samples' was set, and two-way ANOVA analysis was performed to identify differences and interactions between gender and condition (hypoxic vs. normoxic).…”
Section: Methodsmentioning
confidence: 99%